Introducing plug-in electric vehicles in public authorities. (March 2016) - Wikström, Martina; Eriksson, Linnea; Hansson, Lisa
Abstract: Plug-in electric vehicles have the potential to contribute to a more energy-efficient and a less fossil dependent road transport system. Swedish local authorities are obligated through legislation to substitute fossil-fuelled vehicles and plug-in electric vehicles offer an alternative for achieving their climate goals. Previous studies assign certain individuals – the policy entrepreneurs – a central role when implementing new technologies in public authorities. By combining the theoretical model of policy entrepreneurs with the theory of outcome indicators, this paper demonstrates how the policy entrepreneur affects and accelerates the introduction of plug-in electric vehicles in local public authorities. The result shows that policy entrepreneurs undertake actions to inform and persuade the decision-makers and raise the issue on the political agenda. The policy entrepreneurs assess the travel demand, find appropriate applications and supervise the deployment process. The policy entrepreneurs inform and inspire vehicle users as a way to ensure acceptance and to increase usage. There are examples of policy entrepreneurs that have accomplished changes in policies governing vehicle use to favour the plug-in electric vehicles. Practical experiences legitimate the policy entrepreneurs when involving local society. The policy entrepreneurs consolidate the new technology within policy documents, amongst the users and in the surrounding society.